1993
DOI: 10.1002/bjs.1800800417
|View full text |Cite
|
Sign up to set email alerts
|

Detection and significance of occult metastases in node-negative breast cancer

Abstract: Detection and significance of occult metastases in node-negative breast cancer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
118
1
2

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(122 citation statements)
references
References 22 publications
1
118
1
2
Order By: Relevance
“…However, 15 -30% of node-negative patients suffer from a recurrence within 5 years (Fisher et al, 1983;Giuliano et al, 1995;Saimura et al, 1999). Previous studies have reported that routine haematoxylin and eosin (H&E) staining analysis of axillary lymph nodes may miss micrometastases in the range of 9 -25% of patients that can be readily detected by serial sectioning (International (Ludwig) Breast Cancer Study Group, 1990;Mascarel et al, 1992;Nasser et al, 1993) and immunohistochemical staining (Mascarel et al, 1992;Hainsworth et al, 1993;Nasser et al, 1993;Cote et al, 1999). However, these methods are too cumbersome, too time-consuming, and too costly to be used in routine examinations (Lockett et al, 1998).…”
mentioning
confidence: 99%
“…However, 15 -30% of node-negative patients suffer from a recurrence within 5 years (Fisher et al, 1983;Giuliano et al, 1995;Saimura et al, 1999). Previous studies have reported that routine haematoxylin and eosin (H&E) staining analysis of axillary lymph nodes may miss micrometastases in the range of 9 -25% of patients that can be readily detected by serial sectioning (International (Ludwig) Breast Cancer Study Group, 1990;Mascarel et al, 1992;Nasser et al, 1993) and immunohistochemical staining (Mascarel et al, 1992;Hainsworth et al, 1993;Nasser et al, 1993;Cote et al, 1999). However, these methods are too cumbersome, too time-consuming, and too costly to be used in routine examinations (Lockett et al, 1998).…”
mentioning
confidence: 99%
“…One possible explanation for this phenomenon is that traditional histological evaluation of ALND specimens underestimates the true rate of lymph node metastases (10)(11)(12)(13)(14). Axillary nodal status may be important in selecting patients particularly with small (pT1) tumors for adjuvant systemic therapy (4,20).…”
Section: Discussionmentioning
confidence: 99%
“…Axillary nodal status may be important in selecting patients particularly with small (pT1) tumors for adjuvant systemic therapy (4,20). Serial or step sectioning substantially improves the staging accuracy of ALND, and this may be further improved by IHC (10)(11)(12)(13)(14). Detailed pathological examination of all nodes removed by ALND is clinically unfeasible, but a focused and detailed evaluation of the nodes most likely to harbor metastasis removed by SLNB may be feasible and cost-effective (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies on the prognostic significance of micrometastases in ALND before introduction of the sentinel node biopsy showed that patients with axillary micrometastases had higher recurrence rates and lower overall survival [11][12][13][14], others however demonstrated no such difference [15,16]. Although most studies with larger sample sizes and longer follow-up tend to show a negative effect of micrometastatic disease on overall and disease free survival [17,18], comparison between these retrospective studies and extrapolation to patients with SNB is hampered by different inclusion criteria and large technical variances in the assessment of micrometastases.…”
Section: Introductionmentioning
confidence: 99%